Global attractivity in a genotype selection model - Xiaoping Li (International Journal of Mathematics and Mathematical Sciences)
We obtain a sufficient condition for the global attractivity of the genotype selection model yn+1=yneβn(1−2yn−k)/(1−yn+yneβn(1−2yn−k)), n∈ℕ. Our results improve the results established by Grove et al. (1994) and Kocić and Ladas (1993).